2020
DOI: 10.3389/fonc.2020.595718
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Disulfiram Chelated With Copper Inhibits the Growth of Gastric Cancer Cells by Modulating Stress Response and Wnt/β-catenin Signaling

Abstract: Disulfiram (DSF) is a well-known drug for alcohol abuse. In recent decades, DSF has been demonstrated to exhibit anti-tumor activity; DSF chelated with copper shows enhanced anti-tumor effect. Our goal was to explore the effect of DSF/Cu complex on the growth and metastasis of gastric cancer (GC) in vitro and in vivo. DSF/Cu complex suppressed the proliferation, migration of MKN-45 and BGC-823 GC cells. Furthermore, DSF/Cu treatment reduced the tumor volume in GC mouse models with a tumor suppression rate of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 59 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…A much-debated question is whether copper up or down regulated the level of C-myc. The previous study has found that increasing intracellular copper ion concentration through disulfiram(DSF) leads to a decrease in the expression of β-catenin and C-myc, two important molecules of the Wnt pathway, thereby inhibiting tumor growth [ 66 ]. However, a more recent research argued that the Copper elevates C-myc stability by promoting phosphorylation at its threonine 58 and serine 62 sites [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…A much-debated question is whether copper up or down regulated the level of C-myc. The previous study has found that increasing intracellular copper ion concentration through disulfiram(DSF) leads to a decrease in the expression of β-catenin and C-myc, two important molecules of the Wnt pathway, thereby inhibiting tumor growth [ 66 ]. However, a more recent research argued that the Copper elevates C-myc stability by promoting phosphorylation at its threonine 58 and serine 62 sites [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor efficacy of DSF depends on the presence or absence of Cu ions, as demonstrated in several studies [ 10 , 12 , 21 , 26 , 29 , 32 , 33 ]. Some studies showed that DSF metabolites chelate Cu ions to form CUET in vivo and in vitro [ 14 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that DSF/Cu inhibits the growth of GC cells by modulating the stress response and Wnt/β-catenin/NF-κβ signaling [ 26 , 27 ]. Consistent with our study, these studies found that DSF/Cu induced anti-GC activity through the joint action of several pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, disulfiram (DSF) was an approved drug for anti-alcoholism medication and accumulating evidence suggested DSF, in combination with copper, showed excellent antitumor activity in multiple cancers, including GC ( 66 ). For example, DSF/Cu complex exhibited antitumor activity against GC cells via modulating the stress response, glycolysis, S6K1, c-Myc and Wnt/β-catenin signaling ( 67 , 68 ). DSF/Cu also induced apoptosis through reactive oxygen species (ROS)/mitogen-activated protein kinase pathway ( 69 ).…”
Section: Discussionmentioning
confidence: 99%